PENENTUAN SEKTOR EKONOMI UNGGULAN DENGAN ANALISIS OVERLAY DI KABUPATEN TRENGGALEK DAN KABUPATEN PACITAN - Widodo, Anggraini Ananda; Marseto, Marseto (Al-Buhuts, 2023)
The purpose of this research is to identify leading sectors, understand the characteristics of economic sectors, understand the grouping of economic sectors and understand the role of economic sectors in regional economic recovery and increasing economic growth. The research method used in this study uses quantitative analysis using the LQ, MRP and Klassen Typology analysis methods, followed by overlay analysis to reach conclusions. According to the results of the calculation of Trenggalek and Pacitan Regencies, 9 sectors and 8 sectors of the LQ calculation base, 10 sectors and 7 sectors are superior to the acquisition of MRP calculations, 5 sectors and 5 sectors are included in quadrant I of the Klassen Typology acquisition. Based on these results, Trenggalek Regency has a real estate sector, education services, and health services while Pacitan Regency has a construction and other services sector which is one of the sectors that achieved positive results in the three research methods. Therefore, according to the overlay analysis, it is a leading economic sector that can be used to drive the economy due to the covid pandemic.